Pengembangan Media Pembelajaran Fiqih Ibadah Menggunakan Metode Sosio Drama Berbasis Youtube - Handoko Hrp, Fiki Robi; Mardianto, Mardianto; Mahariah, Mahariah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
21st century education is often referred to as 4C, one of which includes critical thinking and problem-solving skills. The research will examine the effectiveness of developing learning media using YouTube-based socio-drama methods in fiqh subjects. The research method used is the Research and Development Method with a 4D approach developed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel. The research results show that (1) media development uses the 4D method with 4 stages: Define (initial analysis of problems, students, tasks, concepts, and formulation of learning objectives); design (product design); develop (validation test by material, media, and language experts, then carry out limited trials); Disembodied (extensive test stage for Mts. Al-Wasliyah 48 Binjai class VII students): as many as 32 people. (2) In the feasibility test, the scores obtained from material experts were 98%, media experts were 90%, and language experts were 97%, with an average percentage of 95%, and they entered the very feasible category. (3) The results of the limited practicality test carried out on 5 students got a score of 77.27%; the broad practicality test carried out on 32 students got a score of 87.60% in the practical category; and the recapitulation results got an average score of 82.44% in the very practical category. (4) The effectiveness test was carried out by implementing Fiqh Worship learning media using the YouTube-based socio-drama method with a normalized gain score (N-Gain) of 0.58% and was shown in the effective category